Drug-coated stent as well as preparation method and application thereof

The PMEA-based drug-loading suspension is applied to the bile stent through liquid flame spraying technology, which solves the problem of clogging and failure of bile stent due to bile sludge adhesion, achieves higher adhesion, density and wear resistance, and extends the service life of the stent.

CN119524218APending Publication Date: 2025-02-28NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1

Patent Information

Application Number
CN202311096691.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing biliary stents are prone to clogging and failure due to bile sludge attachment, and traditional modification methods are complex and have limited effects.

Method used

The PMEA-based drug-loading suspension was coated on the outer surface of the NiTi alloy shape memory stent by liquid flame spraying technology to prepare a drug-coated stent to improve the adhesion, density and wear resistance of the stent.

Benefits of technology

It improves the anti-adsorption protein and antibacterial properties of the stent surface, extends the patency cycle of the stent, reduces the risk of bile duct reblocking and stent failure, and is suitable for the treatment of clinical hepatobiliary diseases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524218A_ABST
    Figure CN119524218A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a drug-coated stent. The preparation method comprises the following steps: preparing a NiTi alloy shape memory stent; preparing a PMEA-based drug-loaded coating suspension slurry; and coating the prepared PMEA-based drug-loaded coating suspension slurry on the outer surface of the NiTi alloy shape memory stent by adopting a liquid flame spraying mode to obtain the drug-coated stent. The invention also discloses the drug-coated stent prepared by the preparation method and application thereof. The liquid flame spraying technology is used for stent surface modification, the prepared drug-coated stent has a good effect of preventing protein adsorption, bile duct re-blockage and stent failure can be better prevented by combining the drug-coated stent with antibacterial drugs, and the drug-coated stent can be used for clinical treatment of liver and gall diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional coatings, and in particular to a drug-coated stent and a preparation method and application thereof. Background Art

[0002] Hepatobiliary diseases are one of the common diseases that seriously threaten human life and health today, with high morbidity and mortality, and many complications. Percutaneous transhepatic biliary stenting is an important palliative treatment method that can effectively relieve jaundice, create conditions for further radiotherapy and chemotherapy, improve the patient's quality of life, and prolong survival.

[0003] Biliary stents are usually used to form channels in the bile duct and can be used for interventional treatment of benign bile duct stenosis caused by liver transplantation, chronic pancreatitis, stenosis after bile duct surgery, primary sclerosing cholangitis, malignant bile duct stenosis caused by tumor compression, and bile duct stenosis of unknown nature.

[0004] Biliary stents can be divided into two categories based on materials, namely polymer stents and metal stents. Among them, polymer stents have poor mechanical properties and a short patency period, generally 4-5 months. Compared with polymer stents, metal stents have good mechanical properties and high surface finish, can be covered by biliary epithelial cells, and bacteria are less likely to adhere because they are not easily displaced or blocked. The patency period is generally about 1 year.

[0005] Metal stents are generally made of stainless steel wire, tantalum wire, nickel-titanium alloy wire and other materials. Among them, stents such as stainless steel wire that do not have shape memory need to be expanded with a balloon during implantation. This process requires the stent to be first shrunk and put on the balloon. After the guide wire is placed to the affected area, the stent is supported and pressed against the inner wall of the affected area through the balloon. The stent undergoes plastic deformation twice in this process, and its mechanical properties are reduced.

[0006] Due to its unique superelasticity, shape memory, good biocompatibility and corrosion resistance, nickel-titanium alloy (NiTi alloy) can be used to prepare self-expanding stents that can automatically expand at body temperature and maintain a close fit with the inner wall of the pipe, and are not easily displaced during movement.

[0007] However, due to the adhesion of bile sludge, the bile duct and stent are prone to blockage and failure. The main components of bile sludge are protein, bacteria, calcium palmitate and calcium bilirubin. In order to prevent the bile duct and stent from being blocked and failing, the metal stent is usually modified. The modification methods of metal bile duct stents are mainly divided into coating, inert coating and drug loading modification. The fully coated stent is mainly to prevent the bile duct endothelial tissue from clogging the stent, but the coated part is easy to block the opening of the cystic duct and pancreatic duct, causing an increased risk of acute cholecystitis and pancreatitis. The surface of the stent is coated with an inert coating, which can form a protective layer between the stent and the body fluid environment, thereby improving corrosion resistance and biocompatibility.

[0008] The drug-eluting stent consists of a bare metal stent, a drug-eluting material, and a drug. It uses the bare metal stent platform to carry drugs such as anti-protein adsorption and anti-bacterial adhesion to prevent restenosis in the stent. Currently, there are few studies on drug-eluting coated biliary stents that prevent biliary sludge accumulation.

[0009] The drug-loaded materials of drug-loaded stents are mostly high molecular polymers. Natural polymers such as gelatin, collagen, and chitosan are abundant in source, weak in antigenicity, good in biocompatibility, excellent in biodegradability, and non-toxic in products; polyester synthetic polymer materials such as poly (2-methoxyethyl acrylate) (PMEA), polylactic acid, polycaprolactone, and polyethylene glycol have controllable properties, are easy to chemically modify, and the final degradation products are usually non-toxic.

[0010] The anti-protein adhesion performance of PMEA in the blood environment has been studied in many literatures. In the body fluid environment, the surface will adsorb bound water, so it can resist protein adhesion, thereby preventing subsequent microorganisms from forming colonies and producing bile sludge.

[0011] The patent document with publication number CN115024870A discloses a coating-modified drug-loaded bile duct stent, including a stent body, and a controlled-release drug delivery layer and a SrHPO4 modified coating sequentially coated on the outside of the stent body; the stent body is a columnar grid stent woven from a double-layer composite monofilament, and the double-layer composite monofilament includes a poly-L-lactic acid inner core and a magnesium-neodymium alloy outer sheath coated on the outside of the poly-L-lactic acid inner core. Compared with traditional stents, the bile duct stent of this invention has significantly improved support force, prolonged support time, and good biocompatibility and degradability. However, this invention mainly prepares a drug-loaded bile duct stent by improving the stent, and the preparation process is relatively complicated.

[0012] Thermal spraying has the advantages of easy operation, high cost-effectiveness and environmental protection. It has been widely used in many fields, such as drug delivery systems using polymer materials. Among them, the processing temperature of liquid flame spraying is the lowest among thermal spraying technologies, and it has certain advantages in manufacturing polymer coatings.

[0013] Although thermal spraying has been successful in depositing polymer coatings, it has not yet been found that thermal spraying technology can be used to prepare drug coatings on the surface of stents. Therefore, if thermal spraying technology can be used for stent surface modification to construct drug coatings on the surface of biliary stents and achieve sustained release of drugs, it will be of great significance for the treatment of biliary diseases. Summary of the invention

[0014] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a drug coating, wherein a PMEA-based drug-loaded suspension slurry is coated on the outer surface of a NiTi alloy shape memory stent by liquid flame spraying, thereby preparing a drug-coated stent. The method of the present invention is simple, has a short preparation cycle, and has great advantages in clinical applications.

[0015] A method for preparing a drug-coated stent comprises the following steps:

[0016] (1) Preparing a NiTi alloy shape memory stent;

[0017] (2) preparing a PMEA-based drug-loaded coating suspension slurry;

[0018] (3) The PMEA-based drug-loaded coating suspension prepared in step (2) is coated on the outer surface of the NiTi alloy shape memory stent prepared in step (1) by liquid flame spraying to obtain a drug-coated stent.

[0019] The present invention uses liquid flame spraying technology for stent surface modification, and applies PMEA-based drug-loaded coating suspension slurry on the outer surface of NiTi alloy shape memory stent through liquid flame spraying technology to prepare drug-coated stent. Compared with coatings prepared by traditional coating technology, thermal spray coatings have higher adhesion, density and wear resistance, and can withstand complex stress states.

[0020] The drug-coated stent body prepared by the present invention is a NiTi alloy shape memory stent, which has good biocompatibility and corrosion resistance. The outer surface of the stent is coated with a PMEA-based drug-loaded suspension slurry, which has a good effect of preventing protein adsorption. Combined with antibacterial drugs, it can better prevent bile duct re-blockage and stent failure, and can be used for the treatment of clinical hepatobiliary diseases.

[0021] Preferably, the NiTi alloy shape memory bracket is prepared by laser selective melting printing method.

[0022] The present invention adopts laser selective melting to print NiTi alloy shape memory stent, which can be customized and has a short preparation cycle, which has great advantages in clinical applications.

[0023] Preferably, the average diameter (D50) of the NiTi alloy powder used to prepare the NiTi alloy shape memory bracket by the laser selective melting printing method is 20 to 55 μm, the laser power is 60 to 240 W, the scanning speed is 400 to 1000 mm / s, the scanning spacing is 30 to 90 μm, the powder thickness is 20 to 40 μm, and the oxygen content in the laser selective melting forming chamber is 1 to 200 ppm.

[0024] Preferably, the preparation steps of the PMEA-based drug-loaded coating suspension slurry are:

[0025] (1) adding 1,4-dioxane to MEA to obtain a mixed solution, adding an initiator dropwise to the mixed solution under an inert atmosphere, stirring, and performing a polymerization reaction to obtain a PMEA precursor solution;

[0026] (2) adding the PMEA precursor solution obtained in step (1) to the precipitant, stirring, removing the supernatant after standing, and drying the remaining product to obtain PMEA colloid;

[0027] (3) The PMEA colloid obtained in step (2) is diluted with an organic solvent, and then a drug carrier filled with an antifouling agent is added to obtain a PMEA-based drug-loaded suspension.

[0028] Preferably, in step (1), the molar ratio of 1,4-dioxane to MEA is 0.53-0.67:1.

[0029] In step (1), an initiator is added dropwise to the mixed solution under an inert atmosphere to exhaust the air in the reaction system and prevent an oxidation-reduction reaction from occurring when the initiator is added dropwise, thereby causing the initiator to become ineffective.

[0030] Preferably, in step (1), the initiator is AIBN, and the mass of AIBN is 0.1-2% of the mass of MEA.

[0031] When the mass ratio of AIBN to MEA is 0.1-2%, the contact angle of PMEA colloid is the smallest, the adsorption force on other substances is small, and the blood compatibility is good. When the initiator concentration in the PMEA precursor solution decreases, the reaction rate slows down; when the initiator concentration in the PMEA precursor solution increases, there is no significant change.

[0032] Preferably, the dropping speed of the AIBN is 1 to 10 mL / min.

[0033] Preferably, in step (1), the stirring speed is 120-260 r / min, the polymerization temperature is 60-80° C., and the time is 5-8 h.

[0034] The reaction temperature of MEA and 1,4-dioxane of the present invention is 60-80°C. When the reaction temperature is lower than 60-80°C, the amount of the product obtained by polymerization is very small; when the reaction temperature is higher than 60-80°C, the interfacial free energy increases and the hydrophilicity of the material decreases.

[0035] The reaction time of MEA and 1,4-dioxane of the present invention is 5 to 8 hours. If the reaction time is longer than 5 to 8 hours, the interfacial free energy of the reaction product increases; if the reaction time is shorter than 5 to 8 hours, the polymerization of the reactants is incomplete.

[0036] Preferably, in step (2), the precipitant comprises at least one of n-hexane or petroleum ether.

[0037] Since the copolymer obtained after the reaction and the unreacted monomers are dissolved in the solvent, a precipitant needs to be added to precipitate the copolymer obtained after the reaction for product extraction.

[0038] Preferably, in step (2), the mass ratio of the PMEA precursor solution to the precipitant is 1:2-3.

[0039] Preferably, in step (2), the stirring speed is 50 to 120 r / min, and the time is 0.2 to 0.6 h.

[0040] Preferably, in step (2), the drying temperature is 80-120° C. and the drying time is 6-12 hours.

[0041] Preferably, in step (3), the organic solvent comprises methanol or 1,3-propylene glycol.

[0042] Preferably, in step (3), when the organic solvent is methanol, the mass ratio of the PMEA colloid to methanol is 150-160:1.

[0043] PMEA colloid is a material with good anti-protein adsorption and antibacterial properties. It contains a large amount of ethylene glycol side chains. The ethylene glycol side chains can not only reduce the adsorption force of the material surface to various components in the blood, but also have very little interaction with the proteins in the blood. Due to its large steric hindrance, the ethylene glycol side chains can effectively prevent protein adsorption. PMEA is a hydrophilic material with low interfacial free energy, which is closer to the interfacial free energy of the vascular endothelium, thus greatly hindering the adsorption and denaturation process of proteins.

[0044] Since the inert atmosphere is used in the process of preparing PMEA in the present invention to prevent the oxidation of the initiator, the purity of the prepared PMEA colloid is significantly improved and the hydrophilic property thereof is also improved.

[0045] Preferably, in step (3), the antifouling agent comprises at least one of potassium diformate, antimicrobial peptides, siloxane sulfobetaine, schisandra chinensis lignans, chlorhexidine, ethylparaben or triclosan.

[0046] Preferably, in step (3), the drug carrier comprises at least one of polymer hollow microspheres, liposomes, dendrimers, MOFs, COFs, metal oxides or MXenes.

[0047] Preferably, in step (3), the mass ratio of the antifouling agent to the drug carrier is 1:1-100.

[0048] Preferably, in step (3), the content of the antifouling agent in the PMEA-based drug-loaded suspension is 0.005-0.5 wt %.

[0049] Preferably, in the liquid flame spraying process, the supply system for spraying the PMEA-based drug-loaded suspension consists of an atomizing nozzle, a peristaltic pump and compressed air, the spraying raw material flow rate is 20-80 ml / min, the peristaltic pump rate is 30-55 rpm, and the compressed air pressure is 0.15-0.4 MPa.

[0050] Preferably, the parameters of the liquid flame spraying process are: O2 as the combustion-supporting gas, the pressure is 0.3-0.5 MPa, the flow rate is 2-4.0 Nm 3 / h; C2H2 is used as fuel gas, the pressure is 0.05~0.4MPa, and the flow rate is 0.5~2Nm 3 / h.

[0051] Preferably, during the liquid flame spraying process, the concentric rotation speed of the NiTi alloy shape memory bracket is 50-500r / min, the spraying distance of the flame spray gun from the outer surface of the bracket is 100-200mm, the moving speed is 400-900mm / s, the spraying angle is 45-135°, and the coating is sprayed 5-10 times.

[0052] The present invention also provides a drug-coated stent prepared by the above-mentioned preparation method. The main body of the drug-coated stent is a NiTi alloy shape memory stent, which has good biocompatibility and corrosion resistance. The outer surface of the stent is coated with a PMEA-based drug-loaded suspension slurry, which has a good effect in preventing protein adsorption. Combined with antibacterial drugs, it can better prevent bile duct re-blockage and stent failure.

[0053] The present invention also provides the use of the drug-coated stent in the treatment of biliary diseases. The drug-coated stent of the present invention has good biocompatibility and corrosion resistance, better prevents the effect of protein adsorption, and can better prevent bile duct re-blocking and stent failure in combination with antibacterial drugs, and has good application prospects and economic benefits in the treatment of biliary diseases.

[0054] Compared with the prior art, the present invention has the following advantages:

[0055] (1) The present invention adopts laser selective melting to print NiTi alloy shape memory stents, which can be customized and has a short preparation cycle, which has great advantages in clinical applications.

[0056] (2) The PMEA colloid prepared by the present invention has high purity, good hydrophilicity and anti-protein adhesion properties, and can effectively prevent the scaffold from adsorbing proteins.

[0057] (3) The present invention adopts liquid flame spraying technology to coat the prepared PMEA-based drug-loaded suspension slurry on the NiTi alloy shape memory stent to prepare a drug-loaded coated stent. Compared with the coating prepared by traditional coating technology, the thermal spray coating has higher adhesion, density and wear resistance, and can withstand complex stress states.

[0058] (4) The drug-coated stent prepared by the present invention is a NiTi alloy shape memory stent with good biocompatibility and corrosion resistance. The outer surface of the stent is coated with a PMEA-based drug suspension slurry, which has a good effect in preventing protein adsorption. Combined with antibacterial drugs, it can better prevent bile duct re-blockage and stent failure, and has good application prospects and economic benefits in clinical hepatobiliary diseases. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 It is a schematic diagram of liquid flame spraying of the present invention.

[0060] Figure 2 This is the infrared spectrum of the PMEA colloid prepared in Example 1.

[0061] Figure 3 The following are SEM images of the drug coatings prepared in the examples and comparative examples attached to Escherichia coli at different times, wherein: Figure 3 a is a SEM image of the triclosan-PMEA-methanol drug coating prepared in Example 1 attached to Escherichia coli at different times, wherein Figure 3 The attachment time of (a-1) was 4 h; Figure 3 The attachment time of (a-2) was 16 h; Figure 3 The attachment time of (a-3) is 28h;

[0062] Figure 3 b is the SEM image of the chlorhexidine-PMEA-methanol drug coating prepared in Example 2 attached to Escherichia coli at different times, wherein Figure 3 The attachment time of (b-1) was 4 h; Figure 3 The attachment time of (b-2) was 16 h; Figure 3 The attachment time of (b-3) is 28h;

[0063] Figure 3 c is the SEM image of the ethylparaben-PMEA-methanol drug coating prepared in Example 3 attached to Escherichia coli at different times, where Figure 3 The attachment time of (c-1) was 4 h; Figure 3 The attachment time of (c-2) was 16 h; Figure 3 The attachment time of (c-3) is 28h;

[0064] Figure 3d is the SEM image of the PMEA-methanol coating prepared in Comparative Example 1 attached with Escherichia coli at different times, where Figure 3 The attachment time of (d-1) was 4 h; Figure 3 The attachment time of (d-2) was 16 h; Figure 3 The attachment time of (d-3) is 28h;

[0065] Figure 3 e is the SEM image of the NiTi alloy bare stent prepared in comparative example 2 attached with Escherichia coli at different times, where Figure 3 The attachment time of (e-1) was 4 h; Figure 3 The attachment time of (e-2) is 16 h; Figure 3 The attachment time of (e-3) is 28h.

[0066] Figure 4 The SEM images of the drug coatings prepared in the examples and comparative examples attached to Bacillus subtilis at different times, wherein: Figure 4 a is a SEM image of the triclosan-PMEA-methanol drug coating prepared in Example 1 attached to Bacillus subtilis at different times, wherein Figure 4 The attachment time of (a-1) was 4 h; Figure 4 The attachment time of (a-2) was 16 h; Figure 4 The attachment time of (a-3) is 28h;

[0067] Figure 4 b is the SEM image of the chlorhexidine-PMEA-methanol drug coating prepared in Example 2 attached to Bacillus subtilis at different times, wherein Figure 4 The attachment time of (b-1) was 4 h; Figure 4 The attachment time of (b-2) was 16 h; Figure 4 The attachment time of (b-3) is 28h;

[0068] Figure 4 c is the SEM image of the ethylparaben-PMEA-methanol drug coating prepared in Example 3 attached to Bacillus subtilis at different times, wherein Figure 4 The attachment time of (c-1) was 4 h; Figure 4 The attachment time of (c-2) was 16 h; Figure 4 The attachment time of (c-3) is 28h;

[0069] Figure 4 d is the SEM image of the PMEA-methanol coating prepared in Comparative Example 1 attached to Bacillus subtilis at different times, where Figure 4 The attachment time of (d-1) was 4 h; Figure 4 The attachment time of (d-2) was 16 h; Figure 4 The attachment time of (d-3) is 28h;

[0070] Figure 4 e is the SEM image of the NiTi alloy bare stent prepared in comparative example 2 attached with Bacillus subtilis at different times, where Figure 4 The attachment time of (e-1) was 4 h; Figure 4 The attachment time of (e-2) is 16 h; Figure 4 The attachment time of (e-3) is 28h.

[0071] Figure 5 The 3D morphology of the drug coating surface prepared in the examples and comparative examples, wherein: Figure 5 a is the 3D morphology of the drug coating surface prepared in Example 1; Figure 5 b is the 3D morphology of the drug coating surface prepared in Example 2; Figure 5 c is the 3D morphology of the drug coating surface prepared in Example 3; Figure 5 d is the 3D morphology of the PMEA-methanol coating surface prepared in Comparative Example 1.

[0072] Figure 6 This is a SEM image of the cross section of the drug-coated stent prepared in Example 1.

[0073] Figure 7 The bile sludge adhesion of the drug-coated stents prepared in the examples and comparative examples after 7 hours of bile circulation, wherein: Figure 7 (a-1) is a SEM image of the triclosan-PMEA-methanol coated stent prepared in Example 1, Figure 7 (a-2) is Figure 7 (a-1) is a partial enlarged view; Figure 7 (b-1) is a SEM image of the chlorhexidine-PMEA-methanol coated stent prepared in Example 2, Figure 7 (b-2) is Figure 7 (b-1) is a partial enlarged view; Figure 7 (c-1) is a SEM image of the ethylparaben-PMEA-methanol coated stent prepared in Example 3, Figure 7 (c-2) is Figure 7 (c-1) Partially enlarged image; Figure 7 (d-1) is the SEM image of the NiTi alloy bare stent prepared in Comparative Example 2, Figure 7 (d-2) is Figure 7 (d-1) is a partial enlarged view. DETAILED DESCRIPTION

[0074] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0075] In the embodiments of the present invention, the following method is used to characterize the performance of the prepared drug coating sample and drug coating stent. The specific detection method is as follows:

[0076] (1) Infrared detection of PMEA colloid: The synthesized PMEA colloid was dissolved in methanol to prepare a methanol solution with a concentration of 0.1 g / ml PMEA colloid. The solution was dripped onto a potassium bromide tablet and dried. After the methanol was completely evaporated, FTIR detection was performed.

[0077] (2) Antibacterial performance test: The drug coatings prepared in the examples and comparative examples were subjected to cell activity tests, and the coatings with an activity higher than 70% were selected for antibacterial experiments. The antibacterial rate of the material was calculated using the plate count method. This result can intuitively reflect the antibacterial performance of the material. The number of colonies on each culture medium was counted, and the antibacterial rate (R) was calculated according to the following formula: R = (the number of colonies in the blank control group - the number of colonies in the experimental group) / the number of colonies in the blank control group × 100%. The cell activity was calculated using the CCK-8 method; the number and morphology of bacteria on the surface of the material were observed using SEM.

[0078] (3) Surface morphology observation: The drug coatings prepared in the examples and comparative examples were blown off the dust on the surface with compressed air, and their surface morphology was observed using a 3D optical profilometer.

[0079] (4) Cross-sectional microscopic morphology observation: Au was sprayed on the cross-section of the drug coating prepared in the embodiment and the comparative example, and the surface microscopic morphology was observed using SEM.

[0080] (5) Protein adhesion test: The drug coatings prepared in the examples and comparative examples were subjected to protein adhesion test using human serum albumin.

[0081] (6) Surface contact angle test: The contact angle between the drug coatings prepared in the examples and comparative examples and water was tested using a contact angle tester to evaluate the hydrophilicity and surface energy of the drug coatings.

[0082] (7) Anti-fouling test: The bile was circulated by a peristaltic pump with a flow rate of 1000 ml / h, which is 24 times the flow rate of a normal person. A 1-hour experiment is equivalent to a 1-day effect in the human body. The coated stents prepared in the examples and comparative examples were placed in the silicone tube of the circulation system. The entire circulation system was placed in a 37°C incubator and circulated for 7 hours. The stents were dried and weighed before and after the circulation, and the amount of bile sludge attached was compared. The attached bile sludge was further observed by SEM.

[0083] Example 1

[0084] The steps for preparing the drug-coated stent of this embodiment are as follows:

[0085] 1. NiTi alloy shape memory bracket was prepared by laser selective melting printing method.

[0086] The SLM parameters for preparing NiTi alloy in this embodiment are as follows: the average diameter (D50) of NiTi alloy powder is 50 μm, the laser power is 100 W, the scanning speed is 800 mm / s, the scanning spacing is 80 μm, the powder thickness is 30 μm, and the oxygen content in the laser selective melting forming chamber is 100 ppm. A bidirectional scanning strategy is adopted, with a 67° rotation between consecutive layers.

[0087] 2. Weigh 20g of MEA and add it to a three-necked flask, then measure 20ml of 1,4-dioxane and pour it into the three-necked flask. Place the three-necked flask in a super constant temperature water bath, adjust the temperature to 75°C, start the stirrer and adjust the stirring rate to keep the stirring rate at about 180r / min, maintain a certain nitrogen inflation rate for 30min, weigh 0.1g of AIBN, dissolve it in 10ml of 1,4-dioxane, stir continuously with a glass rod to fully dissolve the initiator, then add the initiator solution to the constant pressure dropping funnel with the piston in the closed state, slowly rotate the piston of the constant pressure dropping funnel, and drop the initiator solution into the three-necked flask under nitrogen protection, and continuously adjust the dropping speed, and finally control the dropping speed at 5mL / min. After the initiator solution was added dropwise, the dropping funnel was removed, and a ground glass stopper coated with vaseline was inserted into the mouth of the three-necked flask. After reacting for 6 hours, a PMEA precursor solution was obtained.

[0088] 3. Slowly pour the fully cooled PMEA precursor solution into 80ml petroleum ether with a mechanical stirring rate of 80r / min. After stirring, let it stand for a while. After the white liquid becomes slightly clear, pour off the upper liquid, leaving the milky white viscous substance, then add petroleum ether and stir. Repeat the above steps until the poured petroleum ether is a clear liquid after stirring. Finally, scrape the product out and place it in a culture dish, cover it with plastic wrap, poke 5-6 small holes in the plastic wrap, place it in a ventilated place overnight, and then put it in a vacuum oven, dry it at 100℃ under vacuum conditions for about 6 hours, take out the culture dish, and obtain a transparent PMEA colloid.

[0089] 4. Weigh 0.5 g of PMEA colloid and dissolve it in 100 ml of methanol to prepare a 5000 ppm PMEA methanol solution. Then weigh 0.05 g of triclosan and dissolve it in the 5000 ppm PMEA methanol solution to prepare a 500 ppm triclosan-PMEA-methanol solution.

[0090] 5. Use liquid flame spraying to evenly spray triclosan-PMEA-methanol solution on the surface of the stent to prepare a drug-coated stent. The spraying raw material flow rate is 60ml / min, the peristaltic pump rate is 50rpm, and the compressed air pressure is 0.2MPa. O2 is used as the combustion-supporting gas, the pressure is 0.4MPa, and the flow rate is 3Nm3 / h; C2H2 is used as the combustion gas, the pressure is 0.2MPa, and the flow rate is 1Nm3 / h; the concentric speed of the stent is 300r / min, the flame spray gun is 150mm away from the outer surface of the stent, the moving speed is 800mm / s, the spraying angle is 100°, and the number of coating sprays is 6 times. After drying the prepared drug-coated stent in an incubator, sterilize it by ultraviolet light for 24 hours.

[0091] Depend on Figure 2 It can be seen that the polymer prepared in this example is PMEA colloid.

[0092] The triclosan-PMEA-methanol solution was coated on a nickel-titanium substrate to obtain a triclosan-PMEA-methanol drug coating after film formation, and the performance of the triclosan-PMEA-methanol drug-loaded coating was tested.

[0093] Depend on Figure 3 It can be seen that after the E. coli were attached to the triclosan-PMEA-methanol drug coating prepared in this example for 4 hours, 16 hours and 28 hours respectively, the number of E. coli attached to the surface decreased significantly with the increase of the attachment time.

[0094] Depend on Figure 4 It can be seen that after Bacillus subtilis was attached to the triclosan-PMEA-methanol drug coating prepared in this example for 4 hours, 16 hours and 28 hours respectively, the number of Bacillus subtilis attached to the surface decreased significantly as the attachment time increased.

[0095] The antibacterial test of the triclosan-PMEA-methanol drug coating prepared in this embodiment showed that the antibacterial rate of Escherichia coli in 4 hours, 16 hours and 28 hours was 32.88%, 61.7% and 70.59% respectively; the cell activity after 3 days was 131.01%; the antibacterial rate of Bacillus subtilis in 4 hours was 100%, 97.87% and 28 hours respectively; the cell activity after 3 days was 131.01%.

[0096] Depend on Figure 5 It can be seen from a that the surface roughness of the triclosan-PMEA-methanol drug coating prepared in this example is very low.

[0097] The test results of the amount of attached protein of the triclosan-PMEA-methanol drug coating prepared in this example are shown in Table 1. The amount of attached protein of the triclosan-PMEA-methanol drug coating is 0, which indicates that the anti-protein performance of the triclosan-PMEA-methanol coating is outstanding.

[0098] The surface contact angle of the triclosan-PMEA-methanol drug coating prepared in this example was tested, and the surface contact angle of the coating was 65.7°, indicating that the triclosan-PMEA-methanol drug coating has good hydrophilicity.

[0099] Depend on Figure 6 It can be seen that the triclosan-PMEA-methanol coating prepared in this example is evenly and densely combined on the surface of the stent.

[0100] The drug-coated stent prepared in this example was subjected to anti-fouling test, and the test results are shown in Table 1. The amount of bile sludge deposited in the triclosan-PMEA-methanol drug coating was 0.6 mg.

[0101] SEM was used to further observe the bile sludge adhesion of the drug-eluting stent after 7 hours of bile circulation (such as Figure 7 As shown in a), the attachments on the surface of the scaffold are mostly filamentous, which is a mixture of protein and plant fiber. Figure 7 In (a-1), we can see that the bile sludge is attached to the stent surface in clusters. Figure 7 In (a-2), the filamentous structure can be clearly observed, and it can be observed that there are almost no bacteria attached to the triclosan-PMEA-methanol drug coating on the stent, which indicates that the drug-coated stent prepared in this example has good antibacterial properties.

[0102] Example 2

[0103] 1. NiTi alloy shape memory bracket was prepared by laser selective melting printing method.

[0104] The SLM parameters for preparing NiTi alloy in this embodiment are as follows: the average diameter (D50) of NiTi alloy powder is 50 μm, the laser power is 100 W, the scanning speed is 800 mm / s, the scanning spacing is 80 μm, the powder thickness is 30 μm, and the oxygen content in the laser selective melting forming chamber is 100 ppm. A bidirectional scanning strategy is adopted, with a 67° rotation between consecutive layers.

[0105] 2. Weigh 20g of MEA and add it to a three-necked flask, then measure 20ml of 1,4-dioxane and pour it into the three-necked flask. Place the three-necked flask in a super constant temperature water bath, adjust the temperature to 75°C, start the stirrer and adjust the stirring rate to keep the stirring rate at about 180r / min, maintain a certain nitrogen inflation rate for 30min, weigh 0.1g of AIBN, dissolve it in 10ml of 1,4-dioxane, stir continuously with a glass rod to fully dissolve the initiator, then add the initiator solution to the constant pressure dropping funnel with the piston in the closed state, slowly rotate the piston of the constant pressure dropping funnel, and drop the initiator solution into the three-necked flask under nitrogen protection, and continuously adjust the dropping speed, and finally control the dropping speed at 5mL / min. After the initiator solution was added dropwise, the dropping funnel was removed, and a ground glass stopper coated with vaseline was inserted into the mouth of the three-necked flask. After reacting for 6 hours, a PMEA precursor solution was obtained.

[0106] 3. Slowly pour the fully cooled PMEA precursor solution into 80ml petroleum ether with a mechanical stirring rate of 80r / min. After stirring, let it stand for a while. After the white liquid becomes slightly clear, pour off the upper liquid, leaving the milky white viscous substance, then add petroleum ether and stir. Repeat the above steps until the poured petroleum ether is a clear liquid after stirring. Finally, scrape the product out and place it in a culture dish, cover it with plastic wrap, poke 5-6 small holes in the plastic wrap, place it in a ventilated place overnight, and then put it in a vacuum oven, dry it at 100℃ under vacuum conditions for about 6 hours, take out the culture dish, and obtain a transparent PMEA colloid.

[0107] 4. Weigh 0.5 g of PMEA and dissolve it in 100 ml of methanol to prepare a 5000 ppm PMEA methanol solution. Then weigh 6.25 mg of chlorhexidine and dissolve it in the 5000 ppm PMEA methanol solution to prepare a 62.5 ppm chlorhexidine-PMEA-methanol solution.

[0108] 5. Use liquid flame spraying to evenly spray 62.5ppm chlorhexidine-PMEA-methanol solution on the surface of the stent to prepare a drug-coated stent. The spraying raw material flow rate is 60ml / min, the peristaltic pump rate is 50rpm, and the compressed air pressure is 0.2MPa. O2 is used as the combustion-supporting gas, the pressure is 0.4MPa, and the flow rate is 3Nm3 / h; C2H2 is used as the fuel gas, the pressure is 0.2MPa, and the flow rate is 1Nm3 / h; the concentric speed of the stent is 300r / min, the flame spray gun is 150mm away from the outer surface of the stent, the moving speed is 800mm / s, the spraying angle is 100°, and the number of coating sprays is 6 times. After drying the obtained drug-coated stent in an incubator, sterilize it by ultraviolet light for 24 hours.

[0109] The chlorhexidine-PMEA-methanol solution was coated on a nickel-titanium substrate to obtain a chlorhexidine-PMEA-methanol drug coating after film formation, and the performance of the chlorhexidine-PMEA-methanol drug-loaded coating was tested.

[0110] Depend on Figure 3 b It can be seen that after the Escherichia coli was attached to the chlorhexidine-PMEA-methanol drug coating prepared in this example for 4 hours, 16 hours and 28 hours respectively, the number of Escherichia coli attached to the surface thereof decreased significantly as the attachment time increased.

[0111] Depend on Figure 4 b It can be seen that after Bacillus subtilis was attached to the chlorhexidine-PMEA-methanol drug coating prepared in this example for 4 hours, 16 hours and 28 hours respectively, the number of Bacillus subtilis attached to the surface of the coating decreased significantly as the attachment time increased.

[0112] The antibacterial test of the chlorhexidine-PMEA-methanol drug coating prepared in this embodiment showed that the antibacterial rate of Escherichia coli of the chlorhexidine-PMEA-methanol drug coating was 100% in 4 hours, 100% in 16 hours, and 100% in 28 hours; the cell activity was 76.48% after 3 days; the antibacterial rate of Bacillus subtilis was 100% in 4 hours, 97.87% in 16 hours, and 94.12% in 28 hours; the cell activity was 76.48% after 3 days.

[0113] Depend on Figure 5 b It can be seen that the surface roughness of the chlorhexidine-PMEA-methanol drug coating prepared in this example is very low.

[0114] The test results of the amount of attached protein of the chlorhexidine-PMEA-methanol drug coating prepared in this example are shown in Table 1. The amount of attached protein of the chlorhexidine-PMEA-methanol drug coating is 0, which indicates that the anti-protein performance of the chlorhexidine-PMEA-methanol coating is outstanding.

[0115] The surface contact angle of the chlorhexidine-PMEA-methanol drug coating prepared in this example was tested, and the surface contact angle of the coating was 54.6°, indicating that the chlorhexidine-PMEA-methanol drug coating has good hydrophilicity.

[0116] The drug-coated stent prepared in this example was subjected to anti-fouling test, and the test results are shown in Table 1. The amount of bile sludge deposited in the chlorhexidine-PMEA-methanol drug coating was 0.2 mg.

[0117] SEM was used to further observe the bile sludge adhesion of the drug-eluting stent after 7 hours of bile circulation (such as Figure 7 As shown in Figure b), the attachments on the surface of the stent are mostly filamentous, which is a mixture of protein and plant fiber. Figure 7 In (b-1), bile sludge can be seen clinging to the surface of the stent in clusters. Figure 7 In (b-2), a filamentous structure can be clearly observed; at the same time, it can be observed that there are almost no bacteria attached to the chlorhexidine-PMEA-methanol drug coating on the stent, which indicates that the drug-coated stent prepared in this example has good antibacterial properties.

[0118] Example 3

[0119] 1. NiTi alloy shape memory bracket was prepared by laser selective melting printing method.

[0120] The SLM parameters for preparing NiTi alloy in this embodiment are as follows: the average diameter (D50) of NiTi alloy powder is 50 μm, the laser power is 100 W, the scanning speed is 800 mm / s, the scanning spacing is 80 μm, the powder thickness is 30 μm, and the oxygen content in the laser selective melting forming chamber is 100 ppm. A bidirectional scanning strategy is adopted, with a 67° rotation between consecutive layers.

[0121] 2. Weigh 20g of MEA and add it to a three-necked flask, then measure 20ml of 1,4-dioxane and pour it into the three-necked flask. Place the three-necked flask in a super constant temperature water bath, adjust the temperature to 75°C, start the stirrer and adjust the stirring rate to keep the stirring rate at about 180r / min, maintain a certain nitrogen inflation rate for 30min, weigh 0.1g of AIBN, dissolve it in 10ml of 1,4-dioxane, stir continuously with a glass rod to fully dissolve the initiator, then add the initiator solution to the constant pressure dropping funnel with the piston in the closed state, slowly rotate the piston of the constant pressure dropping funnel, and drop the initiator solution into the three-necked flask under nitrogen protection, and continuously adjust the dropping speed, and finally control the dropping speed at 5mL / min. After the initiator solution was added dropwise, the dropping funnel was removed, and a ground glass stopper coated with vaseline was inserted into the mouth of the three-necked flask. After reacting for 6 hours, a PMEA precursor solution was obtained.

[0122] 3. Slowly pour the fully cooled PMEA precursor solution into 80ml petroleum ether with a mechanical stirring rate of 80r / min. After stirring, let it stand for a while. After the white liquid becomes slightly clear, pour off the upper liquid, leaving the milky white viscous substance, then add petroleum ether and stir. Repeat the above steps until the poured petroleum ether is a clear liquid after stirring. Finally, scrape the product out and place it in a culture dish, cover it with plastic wrap, poke 5-6 small holes in the plastic wrap, place it in a ventilated place overnight, and then put it in a vacuum oven, dry it at 100℃ under vacuum conditions for about 6 hours, take out the culture dish, and obtain a transparent PMEA colloid.

[0123] 4. Weigh 0.5 g of PMEA colloid and dissolve it in 100 ml of methanol to prepare a 5000 ppm PMEA methanol solution. Then weigh 0.2 g of ethylparaben and dissolve it in the 5000 ppm PMEA methanol solution to prepare a 2000 ppm ethylparaben-PMEA-methanol solution.

[0124] 5. Use liquid flame spraying to evenly spray ethyl paraben-PMEA-methanol solution on the surface of the stent to prepare a drug-coated stent. The spraying raw material flow rate is 60ml / min, the peristaltic pump rate is 50rpm, and the compressed air pressure is 0.2MPa. O2 is used as the combustion-supporting gas, the pressure is 0.4MPa, and the flow rate is 3Nm3 / h; C2H2 is used as the fuel gas, the pressure is 0.2MPa, and the flow rate is 1Nm3 / h; the concentric speed of the stent is 300r / min, the flame spray gun is 150mm away from the outer surface of the stent, the moving speed is 800mm / s, the spraying angle is 100°, and the number of coating sprays is 6 times. After drying the obtained drug-coated stent in an incubator, sterilize it by ultraviolet light for 24 hours.

[0125] The ethylparaben-PMEA-methanol solution was coated on a nickel-titanium substrate to obtain an ethylparaben-PMEA-methanol drug coating after film formation, and the performance of the ethylparaben-PMEA-methanol drug-loaded coating was tested.

[0126] Depend on Figure 3 c It can be seen that after E. coli were attached to the surface of the ethyl paraben-PMEA-methanol drug coating prepared in this example for 4 hours, 16 hours and 28 hours respectively, the number of E. coli attached to the surface thereof decreased significantly as the attachment time increased.

[0127] Depend on Figure 4 c It can be seen that after Bacillus subtilis was attached to the surface of the ethyl paraben-PMEA-methanol drug coating prepared in this example for 4 hours, 16 hours and 28 hours respectively, the number of Bacillus subtilis attached to the surface of the coating decreased significantly as the attachment time increased.

[0128] The antibacterial test of the ethylparaben-PMEA-methanol drug coating prepared in this embodiment showed that the antibacterial rate of Escherichia coli of the ethylparaben-PMEA-methanol drug coating was 14.04% in 4 hours, 29.79% in 16 hours, and 88.24% in 28 hours; the cell activity after 3 days was 106.39%; the antibacterial rate of Bacillus subtilis was 85.62% in 4 hours, 12.77% in 16 hours, and 0% in 28 hours; the cell activity after 3 days was 106.39%.

[0129] Depend on Figure 5 c It can be seen that the surface roughness of the ethylparaben-PMEA-methanol drug coating prepared in this example is very low.

[0130] The surface contact angle test of the ethylparaben-PMEA-methanol drug coating prepared in this example showed that the surface contact angle of the coating was 72°.

[0131] SEM was used to further observe the bile sludge adhesion of the drug-eluting stent after 7 hours of bile circulation (such as Figure 7 c), the attachments on the surface of the scaffold are mostly filamentous, which is a mixture of protein and plant fiber. Figure 7 In (c-1), bile sludge can be seen clinging to the surface of the stent in clusters. Figure 7 In (c-2), a filamentous structure can be clearly observed; at the same time, it can be observed that there are almost no bacteria attached to the ethyl paraben-PMEA-methanol drug coating on the stent, which indicates that the drug-coated stent prepared in this example has good antibacterial properties.

[0132] Comparative Example 1

[0133] 1. NiTi alloy shape memory bracket was prepared by laser selective melting printing method.

[0134] The SLM parameters for preparing NiTi alloy in this comparative example are as follows: the average diameter (D50) of NiTi alloy powder is 50 μm, the laser power is 100 W, the scanning speed is 800 mm / s, the scanning spacing is 80 μm, the powder thickness is 30 μm, and the oxygen content in the laser selective melting forming chamber is 100 ppm. A bidirectional scanning strategy is adopted, with a 67° rotation between consecutive layers.

[0135] 2. Weigh 20g of MEA and add it to a three-necked flask, then measure 20ml of 1,4-dioxane and pour it into the three-necked flask. Place the three-necked flask in a super constant temperature water bath, adjust the temperature to 75°C, start the stirrer and adjust the stirring rate to keep the stirring rate at about 180r / min, maintain a certain nitrogen inflation rate for 30min, weigh 0.1g of AIBN, dissolve it in 10ml of 1,4-dioxane, stir continuously with a glass rod to fully dissolve the initiator, then add the initiator solution to the constant pressure dropping funnel with the piston in the closed state, slowly rotate the piston of the constant pressure dropping funnel, and drop the initiator solution into the three-necked flask under nitrogen protection, and continuously adjust the dropping speed, and finally control the dropping speed at 5mL / min. After the initiator solution was added dropwise, the dropping funnel was removed, and a ground glass stopper coated with vaseline was inserted into the mouth of the three-necked flask. After reacting for 6 hours, a PMEA precursor solution was obtained.

[0136] 3. Slowly pour the fully cooled PMEA precursor solution into 80ml petroleum ether with a mechanical stirring rate of 80r / min. After stirring, let it stand for a while. After the white liquid becomes slightly clear, pour off the upper liquid, leaving the milky white viscous substance, then add petroleum ether and stir. Repeat the above steps until the poured petroleum ether is a clear liquid after stirring. Finally, scrape the product out and place it in a culture dish, cover it with plastic wrap, poke 5-6 small holes in the plastic wrap, place it in a ventilated place overnight, and then put it in a vacuum oven, dry it at 100℃ under vacuum conditions for about 6 hours, take out the culture dish, and obtain a transparent PMEA colloid.

[0137] 4. Weigh 0.5 g of PMEA colloid and dissolve it in 100 ml of methanol to prepare a 5000 ppm PMEA methanol solution.

[0138] 5. Use liquid flame spraying to evenly spray the methanol solution of PMEA on the surface of the stent to obtain a coated stent. The spraying raw material flow rate is 60ml / min, the peristaltic pump rate is 50rpm, and the compressed air pressure is 0.2MPa. O2 is used as the combustion-supporting gas, the pressure is 0.4MPa, and the flow rate is 3Nm3 / h; C2H2 is used as the fuel gas, the pressure is 0.2MPa, and the flow rate is 1Nm3 / h; the concentric speed of the stent is 300r / min, the flame spray gun is 150mm away from the outer surface of the stent, the moving speed is 800mm / s, the spraying angle is 100°, and the number of coating sprays is 6 times. After the obtained coated stent is dried in an incubator, it is sterilized by ultraviolet light for 24 hours.

[0139] After the PMEA-methanol solution is coated on the nickel-titanium substrate to form a film, a PMEA-methanol coating is obtained, and the performance of the PMEA-methanol coating is tested.

[0140] Depend on Figure 3It can be seen that after the E. coli were attached to the PMEA-methanol coating prepared in this comparative example for 4 hours, 16 hours and 28 hours respectively, the number of E. coli attached to the surface thereof increased significantly with the increase of the attachment time.

[0141] Depend on Figure 4 It can be seen that after Bacillus subtilis was attached to the surface of the PMEA-methanol coating prepared in this comparative example for 4 hours, 16 hours and 28 hours respectively, the number of Bacillus subtilis attached to the surface thereof increased significantly with the increase of the attachment time.

[0142] The antibacterial test of the PMEA-methanol coating prepared in this comparative example showed that the antibacterial rate of Escherichia coli of the PMEA-methanol coating was 16.1% after 4 hours, 0% after 16 hours, and 0% after 28 hours; the cell activity after 3 days was 87.57%; the antibacterial rate of Bacillus subtilis was 80.14% after 4 hours, 14.89% after 16 hours, and 0% after 28 hours; the cell activity after 3 days was 87.57%.

[0143] Depend on Figure 5 It can be seen from Figure d that the surface roughness of the PMEA-methanol coating prepared in this example is very low, which indicates that the addition of the antibacterial agent does not affect the surface morphology of the coating.

[0144] The surface contact angle of the PMEA-methanol coating prepared in the comparative example was tested, and the surface contact angle of the coating was 49.6°, indicating that the PMEA-methanol coating has good hydrophilic properties.

[0145] Comparative Example 2

[0146] 1. NiTi alloy shape memory bracket was prepared by laser selective melting printing method.

[0147] The SLM parameters for preparing NiTi alloy in this comparative example are as follows: the average diameter (D50) of NiTi alloy powder is 50 μm, the laser power is 100 W, the scanning speed is 800 mm / s, the scanning spacing is 80 μm, the powder thickness is 30 μm, and the oxygen content in the laser selective melting forming chamber is 100 ppm. A bidirectional scanning strategy is adopted, with a 67° rotation between consecutive layers.

[0148] Depend on Figure 3 It can be seen that after the NiTi alloy bare stent prepared in this comparative example was attached for 4 hours, 16 hours and 28 hours respectively, the number of Escherichia coli attached to the surface thereof increased significantly with the increase of the attachment time.

[0149] Depend on Figure 4It can be seen that after Bacillus subtilis was attached to the surface of the PMEA-methanol coating prepared in this comparative example for 4 hours, 16 hours and 28 hours respectively, the number of Bacillus subtilis attached to the surface thereof increased significantly with the increase of the attachment time.

[0150] The amount of attached protein was tested on the NiTi alloy bare stent prepared in this comparative example. The test results are shown in Table 1. The amount of attached protein of the NiTi alloy bare stent was 5.297, which indicates that the NiTi alloy bare stent is not resistant to protein adsorption.

[0151] The NiTi alloy bare stent prepared in this comparative example was subjected to anti-fouling test, and the test results are shown in Table 1. The amount of bile sludge deposited on the NiTi alloy bare stent was 1 mg.

[0152] After the bare stent was subjected to 7 hours of bile circulation, the attached bile sludge was further observed by SEM. Figure 7 (d-1) The bile sludge is attached to the surface of the stent in clusters. Figure 7 In (d-2), the filamentous structure can be clearly observed, and obvious bacterial colonies can also be found, indicating that the NiTi alloy bare stent has no antibacterial properties.

Claims

1. A method for preparing a drug-eluting stent, characterized in that: The following steps are involved: (1) Preparing a NiTi alloy shape memory stent; (2) preparing a PMEA-based drug-loaded coating suspension slurry; (3) The PMEA-based drug-loaded coating suspension prepared in step (2) is coated on the outer surface of the NiTi alloy shape memory stent prepared in step (1) by liquid flame spraying to obtain a drug-coated stent.

2. The preparation method according to claim 1, characterized in that: The preparation steps of the PMEA-based drug-loaded coating suspension slurry are as follows: (1) adding 1,4-dioxane to MEA to obtain a mixed solution, adding an initiator dropwise to the mixed solution under an inert atmosphere, stirring, and performing a polymerization reaction to obtain a PMEA precursor solution; (2) adding the PMEA precursor solution obtained in step (1) to the precipitant, stirring, removing the supernatant after standing, and drying the remaining product to obtain PMEA colloid; (3) The PMEA colloid obtained in step (2) is diluted with an organic solvent, and then a drug carrier filled with an antifouling agent is added to obtain a PMEA-based drug-loaded suspension.

3. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of 1,4-dioxane to MEA is 0.53-0.67:1; the initiator is AIBN, and the mass of AIBN is 0.1-2% of the mass of MEA.

4. The preparation method according to claim 2, characterized in that: In step (2), the precipitant includes at least one of n-hexane or petroleum ether, and the mass ratio of the PMEA precursor solution to the precipitant is 1:2-3.

5. The preparation method according to claim 2, characterized in that: In step (3), the mass ratio of the PMEA colloid to methanol is 150-160:

1.

6. The preparation method according to claim 2, characterized in that: In step (3), the antifouling agent includes at least one of potassium diformate, antimicrobial peptides, siloxane sulfobetaine, schisandra chinensis lignans, chlorhexidine, ethylparaben or triclosan; the drug carrier includes at least one of polymer hollow microspheres, liposomes, dendrimers, MOFs, COFs, metal oxides or MXenes; the mass ratio of the antifouling agent to the drug carrier is 1:1 to 100, and the content of the antifouling agent in the PMEA-based drug-loaded suspension is 0.005 to 0.5 wt%.

7. The preparation method according to claim 1, characterized in that: The parameters of the liquid flame spraying process are: O2 as the combustion-supporting gas, the pressure is 0.3-0.5 MPa, the flow rate is 2-4.0 Nm 3 / h; C2H2 is used as fuel gas, the pressure is 0.05~0.4MPa, and the flow rate is 0.5~2Nm 3 / h.

8. The preparation method according to claim 7, characterized in that: During the liquid flame spraying process, the concentric speed of the NiTi alloy shape memory bracket is 50-500r / min, the spraying distance of the flame spray gun from the outer surface of the bracket is 100-200mm, the moving speed is 400-900mm / s, the spraying angle is 45-135°, and the coating spraying times are 5-10 times.

9. The drug-eluting stent prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the drug-eluting stent according to claim 9 in treating biliary diseases.

Citation Information

Patent Citations

  • Coating-modified drug-loaded bile duct stent as well as preparation method and application thereof

    CN115024870A

  • Biliary tract implant and manufacturing method thereof

    CN112807493A

  • Biliary tract stent and preparation method thereof

    CN113730663A

  • Composite coating with adjustable release performance of active ingredients and preparation method of composite coating

    CN114246993A

  • Stent to be placed in bile duct and process for producing same

    US20160074149A1

Cited By

  • A multifunctional anti-stenosis drug-coated stent, its preparation method and application

    CN120459385B